1968
DOI: 10.1039/j39680002889
|View full text |Cite
|
Sign up to set email alerts
|

A simple method for the carbonylation of allylic halides with insertion of acetylene

Abstract: A simple procedure for the preparation of methyl 2,5-dienoates from allyl halides, acetylene. carbon monoxide, and methanol at room temperature and atmospheric pressure, based on the formation in sifu of the catalytic nickel complex from nickel chloride, is described. A manganese-iron alloy is used as reducing agent and thiourea is used as ligand for the formation of the complex. A mechanism involving a five-co-ordinated complex is proposed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

1969
1969
2009
2009

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 0 publications
0
10
0
Order By: Relevance
“…423 With propargyl alcohol slightly different products were obtained using palladium on charcoal andPdCl2.424 5. Treatment of acetylene with carbon monoxide under pressure in the presence of [PdCl2(PhCN)2] gives initially cis,cw-muconyl chloride (61), which rapidly isomerizes to the trans,trans product.419 Using low ratios of acetylene to carbon CH=CH-COCI CH=CH-COCI 61 monoxide in the presence of PdCl2, maleic acid derivatives are formed. 425 The very small trace of fumaric acid derivative found suggests that the addition of carbon monoxide to acetylene in the presence of PdCl2 occurs in a stereospecifically cis manner, and that the trace of the fumaric acid deriva- tive is produced subsequently by an independent isomerization.…”
Section: Carbonylationmentioning
confidence: 99%
“…423 With propargyl alcohol slightly different products were obtained using palladium on charcoal andPdCl2.424 5. Treatment of acetylene with carbon monoxide under pressure in the presence of [PdCl2(PhCN)2] gives initially cis,cw-muconyl chloride (61), which rapidly isomerizes to the trans,trans product.419 Using low ratios of acetylene to carbon CH=CH-COCI CH=CH-COCI 61 monoxide in the presence of PdCl2, maleic acid derivatives are formed. 425 The very small trace of fumaric acid derivative found suggests that the addition of carbon monoxide to acetylene in the presence of PdCl2 occurs in a stereospecifically cis manner, and that the trace of the fumaric acid deriva- tive is produced subsequently by an independent isomerization.…”
Section: Carbonylationmentioning
confidence: 99%
“…As we considered the possibility of the catalytic synthesis of methylene lactones by cyclocarbonylation of appropriate acetylenic alcohols, it seemed likely that an appropriate catalyst system could be constructed from a PdCl2/thiourea system which had been reported to catalyze the formation of various methyl maléales, fumarates, muconates, and gluconates from acetylene, air carbon monoxide, and methanol. 2 The system was attractive because, depite the lack of any knowledge of its mechanism of action, it seemed possible that it catalyzed the carboalkoxylation of triple bonds without involving a metal hydride-an involvement we deemed undesirable because of the potential of metal hydrides for catalyzing Pd(II) catalyst system. It gives synthetic results comparable to those achieved by the original PdCL/thiourea system,4 but has the mechanistic advantage of remaining homogeneous for many half-lives.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, allylic halides react readily with acetylene, carbon monoxide, and methanol in the presence of zerovalent nickel, as outlined in Scheme 7.27, to give cis-dienoate esters in 70%-SO% yield. (303) More recently it has been shown that the palladium-catalyzed reaction of perfluoroalkyl iodides with terminal alkynes, carbon monoxide (1 bar), and alcohols, leads to p-perfluoroalkyl alkenoate esters in 50 %-60 % yield. (304) The perfluoroalkyl group invariably adds to the terminal carbon of the alkyne, and in view of the presence of significant quantities of perfluoroalkylalkenes as by-products, a mechanism involving initial formation of perfluoroalkyl radicals has been proposed (Scheme 7.2S).…”
Section: Esters: From Alkynesmentioning
confidence: 99%